Étude de la recherche de l’alignement des boîtes à la palettisation dans une micro-brasserie - Bernard Dufour (Perspectives Interdisciplinaires sur le Travail et la Santé)
This case study, carried out in a microbrewery, demonstrates the importance of box alignment-seeking for workers loading heavy packs onto pallets, as a determinant of musculo-skeletal risk factors. The results indicate that workers spend as much as 70 % more time handling and placing certain packs even though they are not located further away than others. The most restrictive movements, effort duration and postures occur when handling and placing the packs in question. An analysis of the workers’ activities led to a better understanding of the strategies they used to carry out their work effectively and to minimize physical and time constraints. As a result of this study, recommendations were made concerning the development of a new loading site concept.